Khảo sát các điều kiện trích ly suberin từ cạc bần và ảnh hưởng của suberin đến tính chất mực in offset - Đan Thủy, Văn Phạm; Trí, Nguyễn Minh; Tín, Trần Trung; Thảo, Nguyễn Phương (Vietnam Journal of Chemistry, 2016)
In this study, the roots of Sonneratia caseolaris collected in Luc Si Thanh islands, Vinh Long province, Viet Nam were used to isolate suberin. The treated roofs were ground by IKA-M20 Universal Mill (IKA, Germany). The powder was extracted sequentially with dichloromethane, ethanol and water in a Soxhlet apparatus in 8 hours for each solvent. The extractive-free powder was then treated by two different processes. In the first process, the powder was soaked and stirred in NaOH 18 % solution at 110 °C in various investigating time, such as 7, 8, 9, 10, 11 and 12 hours. In the second process, before soaked in NaOH 18 % solution as mentioned in the former, powder was soaked in the mixture of ethanol and water with the ratio of 1:1 in volume. The obtained suberin was characterized by using Fourier Transform Infrared Spectroscopy (FTIR) and thermogravimetric analysis (TGA). The experimental results confirmed that the obtained product was suberin which is in good agreement with the results reported by N. Cordeiro et al. in 2000. The mass of isolated suberin was found to increase with the increase in the soaking time in NaOH 18 % solution for both methods. The effects of suberin on the properties of offset ink including the drying behavior, the flow properties were investigated. The stack test was performed to compare drying behavior of the ink and the suberin-added ink. The stack test showed that the optimum weight percentage of suberin in offset ink is 4 wt%. 4 wt% of suberin in ink also expressed the best flow properties. Keywords. Sonneratia caseolaris, suberin, offset ink.